2004
DOI: 10.2337/diacare.27.2.620
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperglycemia

Abstract: Characteristics of patients with type 2 diabetes in Mexico: results from a large populationbased nationwide survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
2
7
1
1
Order By: Relevance
“…On the other hand, hypertension is also a common cause of CKD and it can be found in 80% of patients with diabetic nephropathy [6,68,70,71]. The incidence of CIN is also higher in patients with diffuse atherosclerotic disease, such as peripheral vascular disease [21,68,69] and previous stroke or myocardial infarction [6]. The role of dyslipidemia in the development of CIN is not clear.…”
Section: Risk Factors For Cinmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hypertension is also a common cause of CKD and it can be found in 80% of patients with diabetic nephropathy [6,68,70,71]. The incidence of CIN is also higher in patients with diffuse atherosclerotic disease, such as peripheral vascular disease [21,68,69] and previous stroke or myocardial infarction [6]. The role of dyslipidemia in the development of CIN is not clear.…”
Section: Risk Factors For Cinmentioning
confidence: 99%
“…A recent observational prospective study showed that acute hyperglycemia represents a risk factor for CIN. In this study of diabetic patients, CIN occurred in 8 out of 19 patients (42%) with hyperglycemia and in 1 out of 19 patients (5.3%) with normal glycemia at the moment of PCI [69]. So it seems to be important to manage blood glucose levels in the periprocedural time.…”
Section: Risk Factors For Cinmentioning
confidence: 99%
“…Elevated glucose levels upon hospital admission (acute hyperglycemia) are a common finding known to have a detrimental effect on the outcome of STEMI [11,12,13] patients, even in the absence of established diabetes mellitus (DM). Although previous studies have shown that elevated glucose levels increase the risk of contrast-induced nephropathy in patients undergoing elective PCI [14,15], only limited data exist regarding the effect of hyperglycemia on AKI in STEMI patients undergoing primary PCI and its relation to the absence of known DM. In the present study, we evaluated the association of admission glucose levels with the occurrence of AKI in a large cohort of consecutive nondiabetic STEMI patients treated with primary PCI.…”
Section: Introductionmentioning
confidence: 99%
“…10 Hyperglycemia and insulin resistance are also common in critically ill patients, even in those without diabetes, 11,12 and are associated with increased morbidity and mortality. [13][14][15][16][17][18][19] Observational trials, after correction for diabetes and other known risk factors, have shown an association between pre-or intraoperative hyperglycemia and postoperative AKI after cardiac surgery, 20,21 between hyperglycemia at cardiac catheterization and contrast nephropathy, 22 and between hyperglycemia during total parenteral nutrition and the development of AKI. 23 Whether the degree of hyperglycemia simply reflects the severity of illness or is actually contributing to the adverse renal outcome can be demonstrated only by a randomized trial comparing correction or tolerance of the elevated blood glucose levels.…”
mentioning
confidence: 99%